IDENTIFICATION AND RANKING OF FACTORS INFLUENCING HUMAN RESOURCE PRODUCTIVITY IN MANUFACTURING SECTOR INDUSTRIES IN AND AROUND MYSORE - Swaroop (International Journal of Research Science and Management, 2015)
Productivity is an economic term describing the relation between the outputs as compared to the inputs needed to produce those outputs. There are different measures of productivity and one of the most widely used measures of productivity is Gross Domestic Product (GDP) per hour worked. The purpose of this study is to identify and study the various factors influencing the human resource productivity in manufacturing sector, to study the extent to which each factor has an impact on the HR productivity and to rank them. The factors influencing the HR productivity were identified from the literature review and by taking expert opinion. These factors were Motivation, Training, Organizational culture, Job clarity, Environment, Job recognition, Salaries and emoluments, Leadership, Job security and job satisfaction. A structured questionnaire was designed to measure each of these dimensions and the primary data was obtained from the employees of five industries. The sample size was taken as one hundred. To examine the reliability of the questionnaire cronbach’s alpha test was conducted which showed that the data had satisfactory reliability. Using Statistical Package for Social Sciences (SPSS) factor analysis was conducted to identify factors influencing human resource productivity in surveyed organizations. Eight factors were extracted. The factors thus obtained were ranked in an order based on the average factor scores obtained for each of the dimension. The various factors ranked according to the average scores are training (4.04), salary (4.013), motivation (4.008), physical environment (3.900), leadership (3.833), recognition (3.812), and organizational culture (3.720), and retirement benefits (3.593)